On balance, an autobiography - Seth, Leila, 1930- (New Delhi : Penguin Random House, 2010)
Autobiographical reminiscences of Leila Seth, b. 1930, Indian lawyer and jurist.
BBS
Hye Trade International
Keywords: Seth, Leila, -- 1930-; Women judges -- India -- Biography; Business & finance